Assistant Independent Self-retaining Truncated Gonioscopy Contact Lens for Minimally Invasive Glaucoma Surgery. Issue 7 (July 2019) - Chalam, Kakarla V.; Ng, Caleb
Abstract : A new assistant independent self-retaining surgical goniolens provide panoramic view of angle during ocular surgery by means of new optical system that consists of 2 fused elements. First element comprises of a concave lens that mirror corneal curvature with 3 stabilizing feet for retention and stability on corneal surface during surgery. Second element comprise of a fused biconvex lens with prism that direct images of the angle through prism into surgical microscope. This surgical lens can be used for visualization of angle during all glaucoma procedures and especially helpful for performing minimally invasive glaucoma surgery.